Comparison of intravitreal ranibizumab monotherapy vs. ranibizumab combined with dexamethasone implant for macular edema secondary to retinal vein occlusion - Liang, Xuemei; Shen, Baiyun; Ou, Zuguo; An, Hongmei; Li, Li (Frontiers in Medicine, 2022)
Purpose: To compare the efficacy and safety of intravitreal ranibizumab (IVR) monotherapy vs. intravitreal ranibizumab plus dexamethasone (IVR+DEX) implant for macular edema (ME) secondary to retinal vein occlusion (RVO). Methods: This prospective, control trial comprised of 96 eyes of 96 patients with ME due to non-ischemic RVO divided into two groups. The IVR monotherapy group consisted of 61 patients (29 with CRVO and 19 with BRVO) treated with ranibizumab with three consecutive loading doses at monthly+pro re nata (three+PRN) regimen. IVR+DEX implant group consisted of 35 patients (19 with CRVO and 16 with BRV) treated with intravitreal ranibizumab plus DEX implant. All eyes underwent best-corrected visual acuity (BCVA, log MAR), central foveal thickness (CFT) and intraocular pressure (IOP). In case of recurrence, each group received initial medication. Results: The changes in logMAR visual acuity from baseline to 12 months. BCVA improved significantly in CRVO patients in the IVR+DEX implant group compared to the IVR group (p=0.03) but not in BRVO patients (p=0.79). The IVR+DEX implant group showed a significant decrease in CFT at 12 months compared to the IVR group (p=0.03) but not in BRVO patients between the two groups (p=0.06). The incidence of high IOP and cataract progression was significantly higher in the IVR+DEX implant group than in the IVR group (p<0.001). Conclusions: In CRVO-ME, treatment with IVR+DEX implant provided a significant improvement in BCVA and reduction in CFT. IOP level and cataract progression were frequent occurrences in combination treated eyes.